The influence of the e-catalogue system on fraud prevention in goods and services procurement in the regional government of Mimika Regency - Maria Suryani Widiastuti; Hasan Basri Umar; Yundhy Hafiziandra (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study aims to examine the influence of the e-catalogue system on fraud prevention in the procurement of goods and services within the Mimika Regency government and to assess how fraud prevention mediates the relationship between e-catalogue implementation and procurement effectiveness. Research/methodology: A quantitative descriptive and explanatory approach was applied using path analyses. Data were collected through structured questionnaires from 50 purposively selected procurement officers and vendors in the study area. Regression and Sobel tests were used to measure the direct and indirect effects of the variables: e-catalogue implementation, fraud prevention, and procurement effectiveness. Results: The findings indicate that the implementation of the e-catalogue system has a significant positive effect on fraud prevention but does not directly affect procurement efficiency. However, fraud prevention significantly influences procurement effectiveness and acts as a mediator between e-catalogue use and procurement performance. The model explains 75.5% of the variance in the procurement effectiveness. Conclusions: The implementation of the e-catalogue system significantly enhanced fraud prevention in public procurement, reinforcing transparency and reducing irregularities. Although it does not directly impact procurement effectiveness, its influence becomes substantial when mediated through strong fraud prevention mechanisms. Thus, digital systems alone are insufficient; effective procurement depends on the integration of technology, robust oversight, and institutional integrity. Limitations: This study is limited to a single regency and relies on self-reported perceptions, which may not capture the full scope of systemic or technical constraints in e-procurement. Contribution: This study contributes to the literature on digital governance and public procurement by highlighting the strategic role of fraud prevention as a mediating factor. This underscores the need for integrated systems that combine digital tools with robust internal control mechanisms to ensure transparent and effective procurement.